(untitled) (Heritage, 2023)
At the end of 1921, the Kumanovo Commercial and Industrial Bank was founded in Kumanovo. From the name of the bank, it is evident that it wanted to deal with economic affairs, but after the unsuccessful work with the mill, it became a discount bank. During the first decade, the Bank operated successfully and brought dividends to its shareholders, although they were not high. This institution also applied innovations in savings, and one of them was thet, in cooperation with the insurance company „Šumadija“, it launched savings that were connected to the client’s life insurance. Over time, the largest creditor of the Bank became the Commercial and Industrial Banc „Vardar“ from Skopje, which had its own representatives in the Bank’s management. Since 1932, the Bank found itself in a difficult situation because it could not collect loans on agricultural promissory notes, and a lot of money placed with certain clients became uncollectible. Therefore, in October 1935, the liquidation of the Bank was initiated, which was successfully completed at the beginning of 1939. All remaining assets after the payment of the creditors were owned by the Commercial and Industrial Bank „Vardar“.